An Empirical Study of Factors Influencing hotel customers' online booking Intention - Abdul Malek H.A. Hazbar; Abdul alem Mohammed; Ataul Karim Ataul Karim (Taez University, 2019)
Given the increasing amount of people who book hotels online, it is important for those in the industry to know which factors influence hotel customers' online booking intention. Consequently, the aim of this study is to investigate the factors that influence the customer's intention to book a hotel online, these factors are: ease of use, social influence, perceived risk, and positive eWOM. A self- administered questionnaire was used to gather data and measure respondents' perceptions, and a total of 214 students at University Utara Malaysia completed the survey. This study used a multiple regression analysis to test the hypotheses. The results showed that social influence has a high positive significant influence on customer's intention to book a hotel online, followed by ease of use and positive eWOM. It was also found that perceived risk has a negative significant influence on the intention to book a hotel online. Based on the results, implications are presented for practitioners.